1988
DOI: 10.1099/0022-1317-69-8-1859
|View full text |Cite
|
Sign up to set email alerts
|

The Intracellular Distribution of Influenza Virus Matrix Protein and Nucleoprotein in Infected Cells and Their Relationship to Haemagglutinin in the Plasma Membrane

Abstract: SUMMARYPre-and post-embedding immune electron microscopy techniques employing ferritin and large and small gold markers to detect cell surface and intracellular antigens respectively, have been combined in a study of influenza virus-infected cells. This has permitted, for the first time, the simultaneous detection of intracellular virus matrix protein (M), nucleoprotein (NP) and membrane haemagglutinin (HA). The technique facilitated an investigation of the possible physical interrelationship between these thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1
2

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 23 publications
2
27
1
2
Order By: Relevance
“…It is generally accepted that the NP protein of influenza A virus accumulates in the nucleus (Watson & Coons, 1954;Lui, 1955). Although there is contradictory evidence as to whether the M 1 protein enters the nucleus, several recent reports clearly demonstrated its migration to the nucleus (Maeno et al, 1977;Beesley & Campbell, 1984;Patterson et al, 1988;Bucher et al, 1989), and one such report described nuclear staining of M1 protein which was characterized by more intense staining of the nucleoli, whereas nuclear staining of NP is characterized by the absence of stain from the nucleoli (Bucher et al, 1989). The association of M protein with the nucleoli was observed in HMV-II cells infected with the influenza C/Yamagata/1/88 strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that the NP protein of influenza A virus accumulates in the nucleus (Watson & Coons, 1954;Lui, 1955). Although there is contradictory evidence as to whether the M 1 protein enters the nucleus, several recent reports clearly demonstrated its migration to the nucleus (Maeno et al, 1977;Beesley & Campbell, 1984;Patterson et al, 1988;Bucher et al, 1989), and one such report described nuclear staining of M1 protein which was characterized by more intense staining of the nucleoli, whereas nuclear staining of NP is characterized by the absence of stain from the nucleoli (Bucher et al, 1989). The association of M protein with the nucleoli was observed in HMV-II cells infected with the influenza C/Yamagata/1/88 strain.…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular location of M1 is still controversial, with some reports describing its detection in both the nucleus and the cytoplasm (Gregoriades, 1973;Oxford & Schild, 1975;Hay & Skehel, 1975;Maeno et al, 1977;Patterson et al, 1988;Bucher et al, 1989) whereas others claim that it is absent from the nucleus (Lazarowitz et al, 1971;Krug & Etkind, 1973). At present, no information is available concerning the intracellular distribution of NP and the M protein during the replication cycle of influenza C virus.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has recently been shown that the M1 protein contains a novel L domain involved in virus budding (21,22). These processes require the M1 protein to interact with the viral glycoproteins HA and NA (1), viral RNP (2,6,46,50,51,53,75), and other viral and host proteins. M1 associates with a number of cellular proteins, including histones (12,76), RACK-1 (cellular receptor of activated C kinase 1) (49), nucleosomes (12), VPS28 (vacuolar protein sorting 28), Cdc42 (cell division cycle 42) (21), protein kinase C (49), extracellular signalregulated kinase (48), and possibly other host proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we postulate that the intracellular tubular aggregates detected in transfected cells are exclusively made up of M1 proteins. We are aware that amorphous M1-containing electron-dense bodies have been detected in influenza virus-infected cells (36), but it should be mentioned that these aggregates do not bear any resemblance to the tubular structures described here. Moreover, to our knowledge, filamentous structures have never been described in cells expressing a recombinant influenza virus M1 protein.…”
Section: M1 As the Key Element In Influenza Virus Particle Formationmentioning
confidence: 99%